1988
DOI: 10.1111/j.1365-3024.1988.tb00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a protective antibody‐dependent response against toxoplasmosis by in vitro excreted/secreted antigens from tachyzoites of Toxoplasma gondii

Abstract: Toxoplasma gondii is a worldwide protozoan parasite which causes severe disease in congenitally infected children and in immunocompromised patients. Besides the well-defined cytoplasmic and membrane antigens of tachyzoites, we felt that excreted/secreted antigens could play a major role in the immune response. We first report the development of a well-controlled procedure for obtaining tachyzoite excreted/secreted antigens (E/SA) in cell-free incubation media. The E/SA immunogenic in human, rat and mouse toxop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
2
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 23 publications
1
58
2
1
Order By: Relevance
“…The previously described assay for serum-stimulated secretion of dense granule proteins was used to induce GRA5 release by extracellular parasites (Darcy et al, 1988) (Coppens and Cesbron-Delauw, unpublished results). Extracellular tachyzoites (1.2 ϫ 10 8 ) were incubated in 1 ml of RPMI medium supplemented with 10% (vol/ vol) heat-inactivated FCS, under mild agitation, for 3 h at 37°C.…”
Section: Fractionation Of Products Released From Extracellular Parasimentioning
confidence: 99%
See 1 more Smart Citation
“…The previously described assay for serum-stimulated secretion of dense granule proteins was used to induce GRA5 release by extracellular parasites (Darcy et al, 1988) (Coppens and Cesbron-Delauw, unpublished results). Extracellular tachyzoites (1.2 ϫ 10 8 ) were incubated in 1 ml of RPMI medium supplemented with 10% (vol/ vol) heat-inactivated FCS, under mild agitation, for 3 h at 37°C.…”
Section: Fractionation Of Products Released From Extracellular Parasimentioning
confidence: 99%
“…We therefore examined the soluble release of GRA5 using an in vitro assay for dense granule secretion (Darcy et al, 1988) (Coppens and Cesbron-Delauw, unpublished results). Extracellular parasites were incubated in a secretory medium for 3 h. Intact parasites were removed by low-speed centrifugation (LSP), and the secreted proteins were recovered in the supernatant (LSS).…”
Section: Gra5 Is Released From the Dense Granules Exclusively As A Somentioning
confidence: 99%
“…In secreted factors of helminthes, which affect the function of host cells, Echinococcus ganulosus secretes a protein, which inhibits neurtophil chemotaxis (Shepherd et al 1991). Darcy et al (1988) reported that excreted/secreted antigens of Toxoplasma gondii could play a major role in the immune response and demonstrated the key role played by excreted/secreted antigens in the protective immune response. Thus, they suggested that these antigens should be of value for the development of new strategies for immunization against toxoplasmosis.…”
Section: Introductionmentioning
confidence: 99%
“…These antigens would induce an immune response against the invading proliferative forms, the tachyzoites, and thus be responsible for concomitant immunity in toxoplasmosis. This hypothesis, which implies the existence of cross-reactive epitopes between antigens excreted-secreted by both stages of the parasite, was the basis for the selection of the target antigens (5,6). This strategy led us to the cloning and expression of the cDNAt encoding the 24-kDa precursor of a 23-kDa native antigen contained in the dense granules of tachyzoites, which presents cross-reacting epitopes with an antigen present in the dense granules of bradyzoites.…”
mentioning
confidence: 99%